HUBUNGAN PHUBBING SMOMBIE DAN NOMOPHOBIA TERHADAP PERILAKU MANUSIA - Resha Khofila; Muhammad Putra Dinata Saragi; M Alif Erhanda Lubis; Fildzah Ghaisani (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The use of gadgets that are not wise and proportional has caused a person's social, mental, and medical problems. Phubbing and smombies are one of the impacts of this problem. Phubbing stands for phone snubbing which refers to the behavior of people who are more focused on using gadgets than interacting with people or the environment around them. Smombie is a person who constantly uses a smartphone, cellphone, or gadget while walking. Or pedestrians who focus on their cellphones without paying attention to their surroundings. While Nomophobia refers to